La Grande Crisi e i suoi effetti sull’Europa - Carlucci, Francesco (Rivista di studi politici internazionali, 2022)
We analyze the financial crisis that hit the world over the last years and we show its effects on the economies of European countries. First, we expose how the crisis began and why; we show the dominant themes and the concatenation of causes that have produced the crisis in the United States and the United Kingdom: the greed of executives of financial institutions, the habit of debt, the excessive monetary liquidity in the world, the housing bubble. Then we explain how the financial crisis has moved into the real economy and in European countries, where it firstly hit banking system, then population and finally sovereign debt. The exposition of the historical development of events gives the opportunity to highlight the weaknesses of global financialeconomic system: the strong financial power in the United States and Europe, the economic and social inequality of population, the tendency to the private and public debt in many countries.